2021
DOI: 10.21608/sjfop.2021.155057
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Aqueous Licorice and Ethanol Moringa Extracts on the Essential Oil Production, and Chemical Constituents of Ajwain (Trachyspermum Ammi) Plants Under Sandy Soil Condition

Abstract: Two field experiments were conducted in 2018/2019 and 2019/2020 cropping season, at the Experimental Farm of Heliopolis Univ., El-Sharqea Governorate, Egypt, in cooperation with the Department of Horticulture, Faculty of Agriculture, Benha University to study the influence of licorice aqueous extract at 0, 10, 20, and 40 g/l concentrations and Moringa ethanol extract at 0, 50, and 100 g/l concentrations and their interaction on essential oil content, essential oil composition, and chemical constituents of ajwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Peter Pears. [37]showed that increasing moringa leaves extract concentration led to increase chlorophyll a, b, carotenoids and total carbohydrates of ajwain plants.…”
Section: -Potassium% In Newly Formed Cormsmentioning
confidence: 93%
“…Peter Pears. [37]showed that increasing moringa leaves extract concentration led to increase chlorophyll a, b, carotenoids and total carbohydrates of ajwain plants.…”
Section: -Potassium% In Newly Formed Cormsmentioning
confidence: 93%